Penerapan Pembelajaran Diferensiasi dan Penyusunan Perangkat Pembelajaran Kurikulum Merdeka di SD Islam I Baledono Purworejo - Budi D., Prasetiyo; Kurniasih, Nila (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
This community service was conducted because SD Islam I Baledono Purworejo had not yet received any information about the Merdeka curriculum at the elementary school level, even though this curriculum should be implemented immediately. Therefore, it was important for us to share information about the Merdeka curriculum at the elementary school level. The Merdeka Curriculum includes differentiated learning, which is essential at the elementary school level. The method used in this community service included preparation, implementation, evaluation, and reporting. After the community service, teachers and principals gained a clear understanding of differentiated learning and the development of Merdeka curriculum learning materials at the elementary school level. This community service was very beneficial for teachers and principals, as they had not yet received information about differentiated learning and the development of Merdeka curriculum learning materials at the elementary school level.